Fossil bacula of five species of Borophaginae (Family: Canidae): Implications for their reproductive biology. - Daniel Varajão de Latorre (PLoS ONE, 2023)
The baculum of mammals offers the opportunity to study the reproductive biology of extinct species given that it is a fossilizable part of the male genitalia and that its size and shape correlate with several aspects of the reproductive biology of extant mammals. Fossil bacula, however, are rare. Currently, bacula have been described from only two extinct species of canids, one from the subfamily Caninae and the other from the extinct subfamily Hesperocyoninae. Here, I describe the bacula of five extinct species of Borophaginae, each of which was found with other skeletal elements that have enabled identification to the species level. Two specimens (Aelurodon ferox and Aelurodon stirtoni) are largely complete, while the baculum from Carpocyon compressus is complete but still embedded in matrix that obscures some of its features. The bacula of Paratomarctus euthos and Desmocyon thomsoni are incomplete, but they provide useful information nonetheless. These borophagine bacula are similar to extant canines in being robust, having a urethral groove, and a simple distal end. These features suggest that the Borophaginae had long-lasting copulation and possibly spontaneous ovulation, similar to the extant canines. However, unlike the straight baculum of extant canines, borophagine bacula are ventrally curved (arched), which is also observed in the hesperocyonine baculum. The implication of this curvature for the reproductive biology of these animals remains unknown.